Reconstruction of the Epistemology of Tahlili Interpretation: A Critical Study of Its Urgency, Special Characteristics, and Existence in the Modern Era - Shiddiq, Abdullah Muhammad; Ibad, Ara Farhanul; Puspitasari, Belia (UIN Sunan Gunung Djati Bandung, 2025)
The tahlili method of interpretation books is characterized by its complex and comprehensive discussion. This makes it a method rich in meaning and considered to possess highly accurate information. This study aims to determine and explore the urgency, special characteristics, and existence of the tahlili method in the modern era, which is both practical and contextual. This study uses a qualitative approach oriented towards theoretical studies. In terms of type, this research is classified as a library study, with data sources drawn from various published literature, both in print and digital media, that are relevant to the research subtheme discussed. The results of this study indicate that the tahlili method faces serious challenges in the modern contemporary era. However, the tahlili method has not lost its existence. Instead, this method continues to adapt by integrating new, more contextual approaches without abandoning its basic principles. Modern exegetical works such as Wahbah az-Zuhaili's al-Munir are concrete evidence that tahlili remains vital as a methodological foundation for text-oriented interpretation while also being open to modern social contexts. Thus, the tahlili method can be seen as an Islamic intellectual heritage that is not only historically valuable but also relevant in responding to the challenges of the times.